Identitas nasional sebagai fondasi karakter bangsa: Kajian atas implementasi nilai – nilai Pancasila dalam kehidupan bermasyarakat di era disrupsi - saputra, yuga dwi (Maliki Interdisciplinary Journal, 2026)
The era of disruption is marked by the acceleration of unexpected technological, social, and cultural changes, placing significant pressure on the sustainability of Indonesia’s national identity. Pancasila, as both the state ideology and the nation’s philosophy of life, holds great potential as a foundation for building resilient character amid the onslaught of these changes. However, this potential is often not fully realized due to a gap between the normative level and daily life practices. This study employs a qualitative approach based on a literature review, analyzing various relevant academic literature, policy documents, and empirical data. The findings indicate that national identity can only function effectively as the foundation of national character if its implementation is contextual, adaptive, and involves cross-sectoral collaboration among the government, educational institutions, families, and civil society. Furthermore, it was found that an approach rooted in local wisdom, integrated with the values of Pancasila, can serve as a bridge between tradition and modernity, thereby ensuring that national. identity is no longer viewed as a historical burden but rather as an adaptive strength relevant to the current generation.